Methods of Da'wah in the Maritime World - Muda, Indra; Rasyid, Daud; Muhibudin, Muhibudin (SABIQ: Jurnal Sosial dan Bidang Pendidikan, 2025)
Maritime communities have distinctive social, cultural, and economic characteristics, such as high mobility, close solidarity, dependence on marine resources, and coastal cultural diversity. This context demands contextual, inclusive, and participatory da'wah methods so that Islamic values ​​can be effectively accepted. This research aims to describe the appropriate da'wah approach method for maritime communities, emphasizing the principles of hikmah (wisdom), mauidhah hasanah (good deeds), and mujadalah bi al-lati hiya ahsan (good deeds), which are adaptive to local religious wisdom. Recommended da'wah methods include contextual lectures in local languages, role models or uswah hasanah (good examples), dialogue and deliberation with Da'i (preachers), a cultural approach to Mad'u (leaders), social services for religious education and economic improvement, innovative media such as community radio, and eco-da'wah that emphasizes marine environmental sustainability. With this approach, da'wah not only functions as a medium for spreading religious teachings, but can also be an instrument for community empowerment, cultural preservation, and protection of marine ecosystems. This study emphasizes the importance of sustainable, humanistic, and contextual da'wah strategies in building a religious, prosperous, and environmentally conscious maritime society.